Applied critical leadership in education : choosing change - Santamaria, Lorri J.; Santamaria, Andres P. (New York : Routledge, 2012)
'Educational researchers, leaders, and practitioners are seeing the increasing need for practical transformative models and theories to address academic, cultural, and socio-economic gaps separating learners at all levels of the educational system. Applied Critical Leadership in Education proposes a shift in leadership and a need to transform status quo educational practices. This book explores a leadership model arising from critical theory and critical pedagogy traditions, and provides examples of applied critical leadership, ultimately expanding ways to think about current leadership models. The authors examine qualitative case studies featuring critical leaders in early childhood education, elementary school, middle school, high school, district level, and higher education, and follow with analysis, discussion, and application questions for readers to address. The cases are followed by critical questions for readers, suggestions for readers to begin conversations around issues of social justice and equity, and brief profiles of other critical leaders engaged in leadership for change around the country. This timely book explores an exciting new leadership model in a time of urgency for critical leadership and sustainable change'--
Includes bibliographical references and index.
Keywords: Educational leadership -- United States; School management and organization -- United States; Education -- Social aspects -- United States